Pemberdayaan Ekonomi Kelompok Pembudidaya Ikan (POKDAKAN) Mina Sari Jaya dari aspek hukum dan perikanan di Kelurahan Tanjung Rhu, Kecamatan Lima Puluh, Pekanbaru - Ulfia Hasanah; Evi Deliana; Indra Lesmana; Rahmad Hendra; Samariadi Samariadi; Ade Burju Roberkat Simanjuntak; Ananda Eka Putri; Andini Innayah Putri; Greis Greis; Gresiana Suyati Gurning; Indah Okvalita; Osha Putri Parawansa; Winda Pertiwi; Zikri Andrian; Zikrilla Mayuli Hoppi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2022)
Economically, most of the residents of RW O6 Tanjung Rhu Village, Lima Puluh District, are middle and lower class residents with irregular income because they do not have a fixed source of income as an economic support. Some residents work as freelance laborers with incomes below Rp. 3,000,000/month. Based on this, the Chairman of the RW and several residents are trying to find alternative businesses or activities that can be used as a source of income and family income. InSeptember 2020, the Mina Sari Jaya Fish Farmers Group (POKDAKAN) was formed, with a catfish farming business plan. Some of the problems experienced are the lack of knowledge and understanding of the Fish Farmers group related to legal aspects in the form of group legality, product legality and product innovation resulting from catfish farming, as well as the lack of optimal group understanding related to fishery aspects in the form of traditional aquaculture patterns so that they have not been able to provide additional income for the family economy. The activities that have been carried out are in the form of Legality Management of Catfish Farming Farmer Groups, increasing group understanding of legal and fisheries aspects through modernization of catfish farming, innovation of processed products made from catfish, namely Catfish nuggets, Halal Label Management and PIRT by-products. The output that has been produced is in the form of Scientific Articles, Haki Registration